Development of test instruments to assess High School Students' critical thinking on the digestive system - Abidin, Zaenal; Soewondo, Aghniyah Mawaddah Mahar Azizi (Jurnal Mangifera Edu, 2025)
Critical thinking is one of the vital 21st-century skills, but many Indonesian students still show low proficiency in this area. To address this gap, it is essential to develop valid and reliable assessment instruments, particularly in science subjects like biology. This study aimed to develop and validate a test instrument to measure high school students' critical thinking skills on the topic of the digestive system. The research followed the ADDIE development model (Analyze, Design, Develop, Implement, Evaluate) and involved 74 eleventh-grade students. The instrument consisted of 30 multiple-choice items based on six critical thinking indicators by Facione: interpretation, analysis, evaluation, inference, explanation, and self-regulation. Validity and reliability were analyzed using the Rasch model with QUEST software. All items were found to be valid and fit the Rasch model, indicating strong construct validity. The item reliability was categorized as excellent (0.93), while student answer consistency was low (0.59), suggesting limited accuracy or care in responses. Most items (70%) were of moderate difficulty. The students' average critical thinking score was 47.25%, with self-regulation being the strongest indicator (63.51%) and analysis and inference being the weakest (35.13% and 38.64%). These results indicate that, although the instrument is effective in measuring critical thinking, students still encounter challenges, particularly in analytical reasoning. Enhancing learning strategies and assessment tools is crucial for improving students’ cognitive development in science education.